Avaliação da estratégia e performance: o caso ULBRA-SM - Coletto, Camila (2008)
This study investigates the organizational strategy and performance of ULBRA (Lutheran University of Brazil), located in Santa Maria. Based on the understanding that the academic community is sensitive to a number of important variables, such as increased competitiveness occurred in recent years, especially the sector of higher education, the strategy s profile is examined from the adaptive model, according to the methodology of Miles and Snow (1978), and separated into three problems: Entrepreneur problem, Engineering issue and administrative problems. The model of performance indicators for structured Kelm (2003) was formed from the perspectives of the balanced scorecard. To achieve the objectives, the methodological procedures involved, first, a series of interviews, to set the strategic profile, with the general director of the campus, the extension coordinator, the research coordinator, educational coordinator, and with the coordinators from the courses of Administration, Architecture, Physiotherapy, Psychology, Law, Aesthetics and Cosmetology, Physical Education and Systems Information. Second, we used a tool set for Kelm (2003) and, to a semi-structured, this tool was adapted. The results were organized from the definition of the profile strategic analyst and organizational performance, were identified as factors of influence in the institution's itself.